Design-Specification Decision-Making in Rural Australia: Precast V In-Situ Concrete - Whyte, Andrew; Bikaun, Graham (University Teknologi PETRONAS, 2012)
The process of design-specification decision making must quickly go beyond an assessment of technical competency; alternatives (proven as structurally sound design solutions) must instead be assessed and chosen based upon factors other than established fit-for-use functionality. This work presents an analysis of two such alternative design solutions, namely precast or in situ concrete, as building component options in civil infrastructure projects in the remote Pilbara region of north Western Australia. The work identifies and compares the merits and demerits of pre-casting civil concrete components that might traditionally be cast in-situ, and examines factors such as increasing labour and accommodation constraints faced by clients and contractors in rural Pilbara that contribute to project durations and costs. The qualitative (pilot study) research methodology adopted, engaged stakeholders involved in the decision making processes in the civil engineering industry and addressed the risks, benefits and opportunities that arise from implementing either in-situ or precast concrete methods. An analysis is presented on how the range of variables encountered on project site influence the decision-making (value management) process from a design engineer’s perspective. The paper concludes that the factors of time and cost are closely related and have a strong influence on the decision making process; the paper presents a practical remote-location decision-making tool to guide design-specification choices in north Western Australia.